2017
DOI: 10.1371/journal.pone.0187591
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of non-communicable diseases and associated risk factors amongst adults living with HIV in Cambodia

Abstract: BackgroundWith rapid expansion of antiretroviral therapy for HIV, there are rising life expectancies among people living with HIV. As a result, co-morbidity from non-communicable diseases in those living and aging with HIV is increasingly being reported. Published data on this issue have been limited in Cambodia. The aim of this study was to determine the prevalence of diabetes mellitus, hypertension and hypercholesterolemia and associated risk factors in adults living with HIV in Cambodia.MethodsThis cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 23 publications
5
34
0
Order By: Relevance
“…The prevalence of hypertension amongst PLHIV was more than 10% in all but one study and was significantly higher in PLHIV than in HIV-negative controls. Studies conducted outside of Africa (with larger sample sizes), in Cambodia, Brazil, Italy and United States of America, 7 , 10 , 11 found higher rates of hypertension in PLHIV than did the studies conducted from Africa. Again, there were marked variations in the prevalence of hypertension in the Malawian and Zimbabwean studies, with rates ranging 10.8% – 44.0% and 1.0% – 8.3%, respectively.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The prevalence of hypertension amongst PLHIV was more than 10% in all but one study and was significantly higher in PLHIV than in HIV-negative controls. Studies conducted outside of Africa (with larger sample sizes), in Cambodia, Brazil, Italy and United States of America, 7 , 10 , 11 found higher rates of hypertension in PLHIV than did the studies conducted from Africa. Again, there were marked variations in the prevalence of hypertension in the Malawian and Zimbabwean studies, with rates ranging 10.8% – 44.0% and 1.0% – 8.3%, respectively.…”
Section: Resultsmentioning
confidence: 66%
“…Other studies also mentioned lifestyle factors (unhealthy diets, physical inactivity, harmful use of alcohol and smoking) as risk factors positively associated with HIV–NCD co-morbidities in PLHIV. 11 , 13 In two studies, other social determinants of health such as gender and employment status were also found to be associated with NCDs in PLHIV, where being female and being unemployed were found to be independently associated with increased risk of development of NCDs 11 , 12 ; however, the effect of these on access to treatment were not assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Study findings from concentrated HIV epidemics that are driven by an increased prevalence of HIV among key populations, point to high prevalence of NCDs among PLHIV [25]. In a Cambodian study among PLHIV, close to half (47.8%) of total study participants had one or more NCDs with 75% unaware of their disease condition prior to the study [26]. A recent modeling report from Kenya estimated 33% of HIV negative individuals and 36% of PLHIV to have at least one NCD.…”
Section: Plos Onementioning
confidence: 99%
“…Cambodia has been making tremendous strides in HIV prevention and control [ 22 ], which has led to the fact that almost all people living with HIV who knew their HIV status were receiving treatment in 2018 [ 1 ]. Further, several studies have revealed a variety of health issues faced by HIV-infected adolescents and adults in Cambodia and made recommendations to effectively tackle these issues [ 23 , 24 ]. However, few studies have been conducted in Cambodia and other Southeast Asian countries to evaluate nutritional status and dietary intake of children living with HIV, especially those of school age.…”
Section: Introductionmentioning
confidence: 99%